George Eliot’s Depiction of the Child in “Silas Marner” (1861) - Khabur Wsu Wsu (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
George Eliot (1819-1880) was a major Victorian novelist who paid attention to important social issues. In “: Silas Marner: the Weaver of Raveloe” (1861) , she addresses the problem of parentless children, embodied in the depiction of Eppie, who is Silas Marner’s adopted daughter, but actually the biological daughter of Molly Farren, who is married in secret to Godfrey Cass. The novel traces more than sixteen years of Eppie's life, making the book seem like a detailed depiction of the image of the child. This paper will examine George Eliot’s representation of the child from these viewpoints: education, family life, parenthood, livelihood, psychological issues, and maturity through the lens of Social Psychology by Sigmund Freud. Moreover, this research is conducted to explore the way Eliot represented the female child, and to prove that she was a committed novelist who sought to instruct not only to entertain the reading public. In her own way, George Eliot demanded that the children had to be protected. Despite all the superficial strength and glories of Britain, it was a weak and vulnerable country from the inside because children were unprotected and defenceless by the British system. Finally, the research delves into the social and the familial life of the Orphaned Eppie who was raised by her adoptive parent Mr. Silas Marner, along with presenting a realistic image of the female child in the Victorian Era by George Eliot.